Machining of 2D materials by ultrasonic embossing - Leow, Teng Wee (Nanyang Technological University, 2023)
The discovery of two-dimensional (2D) materials (E.g., Graphene, Phosphorene and Xenes) in 2004 highlighted the in-plane interatomic interactions displayed in the crystalline materials to be much stronger compared to those along the stacking direction. 2D materials like Graphene exhibit exceptional and extraordinary properties which have attracted worldwide attention. It is internally composed of hexagonally arranged sp2 hybridized atoms that exhibit extraordinary strength, extremely high thermal conductivity and excellent optical properties making it the most prosperous development among many researchers. Herein, the author explores a series of ultrasonic embossing methods capable of imprinting graphene nanostructure on copper and silver substrates. Exfoliating process with two different tapes is used to extract graphene layers from graphite crystals and transfer it onto substrates together with Anodized Aluminum Oxide (AAO). Variations of that process were being experimented to obtain an optimal result. Different embossing parameters were simulated to obtain a high yield of graphene nanoparticles. The results show that exfoliating graphene layers with suitable tapes produce the highest coverage of graphene on the substate and the various factors for ultrasonic embossing (Pressure, Welding Time, Amplitude & Holding Times) contributes significantly to replication depth. The optimized ultrasonic parameters to imprint an array of graphene nanowires is determined, after numerous experiments, to be welding force of 1400N, welding time of 30 s, amplitude of 25% and holding force of 1500N time of 10 s. Hence, the results proved that ultrasonic embossing is effective in shrinking 2D materials to nanoscale for future applications.